O Imperativo da paisagem: projecto para uma casa-galeria em Carreço - José António Peixoto Amorim (2021)
The project of a house-gallery was the starting point for the development of this dissertation. The program required the combination of two distinct but not inseparable functions: a weekend house and an art gallery. This dissertation is composed of two pieces, which although they work as a set, can also be read individually. The first piece translates into texts, images, models, sketches and final drawings, the ideas that, in one way or another, were contributing to the construction of the house-gallery. In the second piece, several texts try to inform the reader of the questions raised by the readings and research of the works of four architects. These two pieces coexist in a logic of mutual contamination. However, it is precisely in this intersperses of fragments of the first and second piece that the dissertation seems to be more coherent.